Predication of Greenhouse Gas Emissions From Gas Flaring Activities in the Niger-Delta Area of Nigeria - Ezeokoro, C. E.; Leton, T. G.; Momoh, Y. (European Journal of Applied Sciences, 2021)
Because of crude-oil exploration activities in the Niger Delta Region, Nigeria as a Country flares about 17.2 billion m3 of natural gas per capita year. An assessment of the historical data on the gas flared between 1965 to 2019 in the Oil-rich Niger-Delta region of Nigeria was carried out. A linear regression model was used to estimate the cumulative volume of gas flared up till the year 2030 using R. The findings show the total CH4 and N2O emission between 1965 to 1974 was 2281324 and 1229722 respectively. There was a steady increase in the estimated CH4 and N2O emissions until 2004. The prediction of cumulative gas flared showed an exponential increase in the cumulative greenhouse gases flared to about 8.8 x 109 metric tons by the year 2030. Overall, the study revealed a striking cause for concern due to the predicted continuous increasing amount of gas flaring and release of greenhouse gas emissions which could have significant effects on the environment.